Comparatively - Retrospective Study of Therapeutic Efficacies of Dapsone Monotherapy and Multidrug Therapy in the Treatment of New Leprosy Cases, Saraburi Province - Samrerng, Sawai (Journal of Health Science of Thailand, 1992)
The auther has conducted comparatively retrospective study of therapeutic efficacies of Dapsone monotherapy and multidrug therapy (MDT) in the treatment of new leprosy cases registered in saraburi province from 1976 – 1988 respectively. Sixty new cases were simply randomized from patient treatment recording cards for allocation into such comparative study. Each group of total sixty cases were randomly recruited into the study according to their age groups, sex and Ridley – Jopling classification of leprosy. They were sub-grouping into each 30 cases of paucibacillary leprosy (PBL) and multibacillary leprosy (MBL) for further comparative study. The indicators or therapeutic indices to be used for this comparative study were clinical improvement, reguarality rate of treatment, falling in bacterial index, occurrence rates of lepra reactions and sides effects, together with relapsing rate and changing of deformity rate. The results of the study has been analyzed, presented and discussed. The overall results revealed much better efficacy of MDT not only in terms of clinical improvement, falling rate of bacterial index and slightly decline in deformity rate but also better safety and acceptability. The author has recommended for further studies such as the study of relapse, evaluating research of multidrug therapy based leprosy control programme under vertical and integrated leprosy control provinces in the region 2, Saraburi and other region as well.